Identifikasi ancaman intelijen siber di Indonesia - Abdillah Satari Rahim; Pujo Widodo; Agus H.S. Reksoprodjo; Alsodiq Alsodiq (CV. AFDIFAL MAJU BERKAH, 2023)
Currently, the cyber domain has become a new strategy that can cause losses that have a strategic impact on a country. The current condition shows that the cyber domain has also been used in intelligence operations. The lack of human resource support, infrastructure support and financial support raises concerns about the readiness to deal with cyber intelligence threats in Indonesia. This research aims to analyse the identification of cyber intelligence threats in Indonesia. This research was conducted using a qualitative method with a case study approach. The analysis was conducted comprehensively through in-depth analysis of the issues raised. The results of this study show that the pattern of cyber intelligence threat identification in Indonesia focuses on deepening the aspects contained in the 9 components of strategic intelligence so as to produce estimates and early detection of potential threats / impacts that can be caused by cyber threats. So that it is necessary to increase information security awareness for the community and the need to increase the quantity and quality of human resources and infrastructure to support the success of cyber intelligence operations so as to produce quality intelligence products.